(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Klippel-Feil Syndrome (KFS) is a complex syndrome comprises of classical clinicaltriad of short neck, limitation of head and neck movements and low posteriorhairline. This syndrome is resulting from failure of the normal segmentation ofcervical vertebra.In this present case in addition to classical clinical triad we have found short stature,scoliosis at cervico- dorsal junction and sprengel deformity of the shoulder. Wedidn’t find any association of hearing impairment, congenital heart disease andrenal abnormalities. There was no any neurological deficit and normal schoolperformance.Patient with KFS usually have good prognosis if cardiopulmonary, genitourinary,auditory problems are identified and treated early. Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 78-81